2012
DOI: 10.1007/s00784-012-0783-4
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five-year atraumatic restorative treatment (ART) approach: a comprehensive overview

Abstract: Background The atraumatic restorative treatment (ART) approach was born 25 years ago in Tanzania. It has evolved into an essential caries management concept for improving quality and access to oral care globally. Results Meta-analyses and systematic reviews have indicated that the high effectiveness of ART sealants using high-viscosity glass ionomers in carious lesion development prevention is not different from that of resin fissure sealants. ART using high-viscosity g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
134
1
31

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(169 citation statements)
references
References 66 publications
3
134
1
31
Order By: Relevance
“…This is also addressed in the present article [1]. So, direct comparison becomes difficult, and now, people start to argue about the (low) quality of the articles from "the other side."…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…This is also addressed in the present article [1]. So, direct comparison becomes difficult, and now, people start to argue about the (low) quality of the articles from "the other side."…”
mentioning
confidence: 79%
“…It would be helpful, though, if a common basis of understanding what ART contributed to dentistry could be formulated. Again, the present overview article [1] could be a starting point.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…O uso combinado de instrumentos manuais e CIV de alta viscosidade torna possível uma melhora na saúde bucal de vários grupos populacionais, pela redução do número de extrações e aumento do número de dentes restaurados, melhora na qualidade de vida da população e satisfação no trabalho do dentista 19 . O CIV de alta viscosidade possui melhor resistência à compressão, ao desgaste e dureza superficial, quando comparado com o CIV convencional [8][9][10][11] . A forma de inserção do CIV nas cavidades dentárias preconizada por cada autor é variável.…”
Section: Introdução|unclassified
“…Specially designed for ART, the high-viscosity GICs have a relatively slow curing and improved mechanical properties compared to low and medium viscosity cements, which has resulted in increased survival of restorations 13 . Recent systematic reviews have shown that the longevity of ART restorations with high-viscosity GICs is similar to the gold standard treatment with amalgam 12,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%